The prevalences of Neisseria gonorrhoeae and Chlamydia trachomatis infections among female sex workers in China - Chen Xiang-Sheng; Yin Yue-Ping; Liang Guo-Jun; Wang Qian-Qiu; Jiang Ning; Liu Qiao; Fu Geng-Feng; Yang Bin; Zhou Yu-Jiao; Shi Mei-Qin; Wang Baoxi (BMC, 2013)
Abstract Background Sexually transmitted infections (STIs) have become a major public health problem among female sex workers (FSWs) in China. There have been many studies on prevalences of HIV and syphilis but the data about Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infections are limited in this population in China. Methods A cross-sectional study was performed among FSWs recruited from different types of venues in 8 cities in China. An interview with questionnaire was conducted, followed by collection of a blood and cervical swab specimens for tests of HIV, syphilis, NG and CT infections. Results A total of 3,099 FSWs were included in the study. The overall prevalence rates of HIV, syphilis, NG and CT were 0.26%, 6.45%, 5.91% and 17.30%, respectively. Being a FSW from low-tier venue (adjusted odds ratios [AOR]=1.39) had higher risk and being age of ≥ 21 years (AOR=0.60 for 21-25 years; AOR=0.29 for 26-30 years; AOR=0.35 for 31 years or above) had lower risk for CT infection; and having CT infection was significantly associated with NG infection. Conclusions The high STI prevalence rates found among FSWs, especially among FSWs in low-tier sex work venues, suggest that the comprehensive prevention and control programs including not only behavioral interventions but also screening and medical care are needed to meet the needs of this population.